Construction of Modified Electrodes with Click Electrochemistry Based on the Hybrid of 4-Azido Aniline and Manganese Phthalocyanine and Electrochemical Pesticide Sensor Applications - KOCA, ATIF (ELECTROCHEMICAL SOC INC, 2018)
Terminal alkynyl substituted manganese phthalocyanine (TA-MnPc) was bounded to 4-azido polyaniline (PANI-N-3) on an indium thin oxide coated glass (ITO) electrode by using click electrochemistry (CEC) method in order to prepare PANI-N-3/TA-MnPc hybrid. Constructed ITO/PANI-N-3/TA-MnPc electrode was characterized with square wave voltammetry (SWV), scanning electron microscope (SEM), and Fourier transform infrared (FT-IR) spectra and then it was investigated as a mimic enzymeless electrochemical sensor (M-Eless-ES) for the pesticide detection. During construction of ITO/PANI-N-3/TA-MnPc electrode, 4-azidoaniline (ANI-N-3) was firstly coated on the ITO surface with the electropolymerization of ANI-N-3 and hereby ITO/PANI-N-3 electrode bearing functional azide groups was prepared. Then TA-MnPc was bounded to the azide groups of ITO/PANI-N-3 electrode with CEC by forming threeazole ring between the azide and terminal alkynyl groups with the catalytic assist of Cu-I ions generated electrochemically on the surface of the electrode. Finally, ITO/PANI-N-3/TA-MnPc electrode was tested as a potential M-Eless-ES for various pesticides. While PANI-N-3/TA-MnPc hybrid interacted with all pesticides, the interaction with the fenitrothion showed completely different voltammetric results than the others. Observation of a new characteristic peak for the fenitrothion sensing illustrated selectivity of the electrode for this pesticide. In addition to the better selectivity, good stability, reproducibility, small detection limit (LOD), high sensitivity, and wide linear range of the electrode indicated possible application of ITO/PANI-N-3/TA-MnPc electrode as a practical pesticide sensor. (C) 2018 The Electrochemical Society.
Keywords: ORGANOPHOSPHORUS PESTICIDES; COBALT PHTHALOCYANINE; ELECTROPOLYMERIZATION; BIOSENSOR; METAL; IMMOBILIZATION; NANOPARTICLES; FENITROTHION; WATER